New Jersey's postsuburban economy - Hughes, James W. (Pinpoints (Series), 2015)
New Jersey has a long history of adapting to a changing economic climate. From its colonial origins to the present day, New Jersey''s economy has continuously and successfully confronted the challenges and uncertainties of technological and demographic change, placing the state at the forefront of each national and global economic era. Based on James W. Hughes and Joseph J. Seneca's nearly three-decade-long Rutgers Regional Report series, New Jersey's Postsuburban Economy presents the issues confronting the state and brings to the forefront ideas for meeting these challenges. From the rural agr.